Rapid induction of p62 and GABARAPL1 upon proteasome inhibition promotes survival before autophagy activation - Sha, Zhe; Schnell, Helena M.; Ruoff, Kerstin; Goldberg, Alfred (The journal of cell biology, 2018)
Proteasome inhibitors are used as research tools and to treat multiple myeloma, and proteasome activity is diminished in several neurodegenerative diseases. We therefore studied how cells compensate for proteasome inhibition. In 4 h, proteasome inhibitor treatment caused dramatic and selective induction of GABARAPL1 (but not other autophagy genes) and p62, which binds ubiquitinated proteins and GABARAPL1 on autophagosomes. Knockdown of p62 or GABARAPL1 reduced cell survival upon proteasome inhibition. p62 induction requires the transcription factor nuclear factor (erythroid-derived 2)-like 1 (Nrf1), which simultaneously induces proteasome genes. After 20-h exposure to proteasome inhibitors, cells activated autophagy and expression of most autophagy genes by an Nrf1-independent mechanism. Although p62 facilitates the association of ubiquitinated proteins with autophagosomes, its knockdown in neuroblastoma cells blocked the buildup of ubiquitin conjugates in perinuclear aggresomes and of sumoylated proteins in nuclear inclusions but did not reduce the degradation of ubiquitinated proteins. Thus, upon proteasome inhibition, cells rapidly induce p62 expression, which enhances survival primarily by sequestering ubiquitinated proteins in inclusions.
Gesehen am 01.10.2019